Emotions attributed to the experience: opinion poll among active consumers of a brand (Human Factors in Design, 2021)
The objective of this research was to verify whether the emotional responses of consumers, evoked through product experience, would be aligned with the value proposition of a clothing brand. To achieve the objective, a field survey was carried out with 400 active clients registered on the website of the study's focus brand. The research was divided in three blocks: (I) demographic profile, (II) free responses and associations and (III) closed answers with multiple choice. The present work confirmed that the current customer base understands the product experience as positive and the emotions most cited by consumers are in line with the brand's value proposition, since the design and communication used evoke, in consumers, pleasure and animation.
Keywords: design; Product experience; Emotions